NEW CHALLENGES FOR OLD PROBLEMS: THE SPECIALIZED NURSE IN REHABILITATION NURSING ON ACCESSIBILITY PROMOTION - Carina Silva; Fábio Oliveira; Marlene Ribeiro; Virgínia Prazeres; Olga Ribeiro (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Background: Accessibility is a crucial element in the quality of life of disabled people, being indispensable for the exercise of their rights. Its effectiveness involves a multidisciplinary team, which should include the nurse specialist in rehabilitation nursing, since it is incumbent that this has to empower the disabled person for the reintegration and exercise of citizenship. Objectives: Reflect on the rights of persons with disabilities; to understand the intervention of the nurse specializing in rehabilitation nursing in accessibility promotion and social inclusion. Main topics under analysis: legislation and plans to promote accessibility and social inclusion; and the intervention of the nurse specializing in rehabilitation nursing in the context of these problems. Conclusion: Accessibility conditions constitute one of the discriminatory factors for disabled people. Thus, the nurse specialized in rehabilitation nursing in parallel with the competent authorities, should face this problem as an urgent opportunity for the promotion of a change.